2022
DOI: 10.1002/mame.202200203
|View full text |Cite
|
Sign up to set email alerts
|

Highly Bio‐Based Unsaturated Polyester Resins with Improved Performance by Incorporating Isosorbide into the Polyester Prepolymer

Abstract: Herein, the successful design of a highly bio‐based family of unsaturated polyester resins (UPRs) is presented, comprising of an isosorbide (ISO) incorporated unsaturated polyester prepolymer (UP) and a reactive diluent of 4‐vinylguaiacol acetyl ester (ACVG). A series of UPs are prepared by copolymerizing ISO with other green monomers, i.e., itaconic acid, ethylene glycol and oxalic acid, in a variation of ISO fraction. The UP/ACVG mixtures exhibit very low viscosity ranging from 2.8 to 3.7 Pa s. After curing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Supporting Information for this article can be found under DOI: https://doi.org/10.1002/cite.202300148. This document includes all experimental procedures, measurements as well as additional references to primary literature relevant for this research [76–99].…”
Section: Supporting Informationmentioning
confidence: 99%
“…Supporting Information for this article can be found under DOI: https://doi.org/10.1002/cite.202300148. This document includes all experimental procedures, measurements as well as additional references to primary literature relevant for this research [76–99].…”
Section: Supporting Informationmentioning
confidence: 99%
“…In some cases, green monomers are used during UPR polymerization. A recent example is the addition of itaconic acid, ethylene glycol, and oxalic acid, which improves the mechanical and thermal properties, such as the glass transition temperature of the neat matrix [66]. On other occasions, this strategy used monomers obtained from recycled polyethylene terephthalate (PET) instead, which promotes the reuse of polymer waste [67].…”
Section: Upr Biocomposite Design Parametersmentioning
confidence: 99%
“…When considering composite design, the reinforcement configuration is a key aspect that affects the mechanical behavior. In the analyzed articles, 13 reinforcement configurations were identified, including woven fabrics [66,[70][71][72][73], non-woven fabrics [74][75][76], short fibers [49,77], powders [78,79], nanofibers [63,80], and nanocrystals [30], or nanostructuration with self-assembled block polymers [81].…”
Section: Upr Biocomposite Design Parametersmentioning
confidence: 99%
“…This viscosity is lower than several bio-based UPRs reported recently, and acceptable for a wide range of applications. 39,44 According to the Hansen's theory, 45 solubility of a compound is strongly influenced by its molecular S2, the PMSD and DE4VG have very similar solubility parameters, suggesting they are highly miscible. The high solubility of the mixture may be the main contributor for the lower viscosity.…”
Section: Synthesis Of De4vg and Pmsd And Characterization Of Their Mi...mentioning
confidence: 99%
“…10 Further works demonstrated that the acetylation of the phenolic hydroxyl group produces 4-vinylguaiacol acetyl ester (AC4VG) can eliminate the inhibition defect of 4VG. 10,43,44 Unfortunately, the acetylation of 4VG required a mass of toxic triethylamine (TEA) as catalyst, and failed to realize a high conversion to AC4VG. Besides, AC4VG only provides a limited number of cross-linkages to improve thermo-mechanical properties of the cured UPR because only the double bond involving to the network formation.…”
Section: Introductionmentioning
confidence: 99%